INVESTIGATING THE USE OF OLD ENGLISH "SECOND PRONOUN" IN ROMEO AND JULIET MOVIE 1996 BY BAZ LUHRMANN AS CORPUS LINGUISTICS STUDY - Siti Hajar Amrina; Lilia Indriani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
This corpus linguistics study is to identify the use of the second pronoun in Romeo and Juliet Movie 1996 by Baz Luhrmann adapted from William Shakespeare's Novel. This movie is about the forbidden love between Romeo and Juliet because of family problems. The beauty of old English is interchangeable especially in literature. English underwent several changes. This change also affects the use of the second pronoun. The development of the pronoun has been a general process, which shows the variations available in what is considered a closed system. Based on Ernest Klein (1966), eight forms of second personal pronouns used by Shakespeare: the singular forms are Thou, Thee, Thy, and the plural forms are Ye, You, Your, and Yours. The objectives of the study are: (1) to identify the use of Old English “second pronoun” in Romeo and Juliet Movie 1996 by Baz Luhrmann adapted from William Shakespeare's Novel; and (2) to know which Old English “second pronoun” is higher and why. This research uses the descriptive qualitative method. The result of the research shows that the movie used old English of second-person pronouns You, Thou, Thee, Thy, Thee, and Thine as a singular pronoun. Based on the findings, the Romeo and Juliet Movie 1996 by Buz Luhrmann adapted from William Shakespeare's novel still uses Old English of second-person pronoun.